(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
A stunning decorative plant native to tropical South America, the Four O’Clock Flower plant (scientifically known as Mirabilis jalapa) is now found across most of the world. Its trumpet-shaped blooms often emerge in the late afternoon, at around four o’clock, and remain open until the following morning, thus the name "Four O’Clock Flower." It is utilized worldwide in traditional medicine to treat a wide range of illnesses. Inflammations, genitourinary diseases, boils, diarrhea, muscle soreness, aphrodisiac, and stomach colic are just a few of the many conditions for which it is utilized. Numerous phytochemical products, including alkaloids, brassicasterol, carbohydrates, flavonoids, glycosides, phytosterols (beta-sitosterol and stigmasterol), oleanolic acid, trigonelline, and ursolic acid, have been identified from this plant’s constituent parts. The anti-inflammatory, antimicrobial (antiviral, antibacterial, and antifungal), antioxidant and cytotoxic, antitumor, antinociceptive, antihistamine and immune modulatory, anti-tubercular induced hepatotoxic effect, antiparasitic, dermatological, hypoglycemic, and antihyperlipidemic qualities of this plant have all been investigated. In the process of creating gold nanoparticles, it is also employed as a reductant.